A longitudinal study of free leptin index in pre-eclamptic pregnancies - Garcés, María Fernanda (2023)
The ratio between circulating levels of leptin and soluble leptin receptor (sOB-R), the free leptin index (FLI), is used as a marker of leptin resistance. Therefore, the aim of our study was to investigate the FLI in mild pre-eclamptic pregnancies in a nested case–control study within a prospective observational study. Circulating levels of leptin and sOB-R levels rise significantly during pregnancy in healthy (p < 0.05) (n = 46) and pre-eclamptic pregnancies (p < 0.05) (n = 20). Serum levels of leptin were significantly higher in pre-eclamptic compared to healthy pregnancies at second and third trimesters of pregnancy (p < 0.05). Additionally, serum levels of sOB-R were significantly lower in pre-eclamptic pregnancies during the second and third trimesters of pregnancy compared to healthy pregnancies (p < 0.05). Moreover, we found that FLI did not vary significantly during pregnancy in healthy women (p > 0.05), while it increases in pre-eclamptic pregnancies (p < 0.05). Indeed, FLI was significantly higher at second and third trimesters of pregnancy in pre-eclamptic compared to healthy pregnancies (p < 0.05). In addition, FLI was significantly higher in the luteal phase compared with the follicular phase of the menstrual cycle in eumenorrheic women (p < 0.05). Receiver operating characteristic (ROC) curve analysis revealed the ability of leptin (AUC = 0.72) and FLI (AUC = 0.67) as a reliable predictor for mild pre-eclampsia during the second trimester of pregnancy. In conclusion, our findings show that FLI were significantly increased in mild pre-eclamptic pregnancies and allowed us to hypothesize that this rise might alter leptin bioavailability and bioactivity which might lead to the sympathetic hyperactivity and the hypertensive disorders during pregnancy.